Lambda-Cyhalothrin Nanosuspension Prepared by the Melt Emulsification-High Pressure Homogenization Method. (5th August 2015) - Pan, Zhenzhong; Cui, Bo; Zeng, Zhanghua; Feng, Lei; Liu, Guoqiang; Cui, Haixin; Pan, Hongyu
Abstract : The nanosuspension of 5% lambda-cyhalothrin with 0.2% surfactants was prepared by the melt emulsification-high pressure homogenization method. The surfactants composition, content, and homogenization process were optimized. The anionic surfactant (1-dodecanesulfonic acid sodium salt) and polymeric surfactant (maleic rosin-polyoxypropylene-polyoxyethylene ether sulfonate) screened from 12 types of commercially common-used surfactants were used to prepare lambda-cyhalothrin nanosuspension with high dispersity and stability. The mean particle size and polydispersity index of the nanosuspension were 16.01 ± 0.11 nm and 0.266 ± 0.002, respectively. The high zeta potential value of −41.7 ± 1.3 mV and stable crystalline state of the nanoparticles indicated the excellent physical and chemical stability. The method could be widely used for preparing nanosuspension of various pesticides with melting points below boiling point of water. This formulation may avoid the use of organic solvents and reduce surfactants and is perspective for improving bioavailability and reducing residual pollution of pesticide in agricultural products and environment.